Theoretical Study of Proton Radiation Influence on the Performance of a Polycrystalline Silicon Solar Cell - Tchouadep Guy Serge; Zouma Bernard; Korgo Bruno; Soro Boubacar; Savadogo Mahamadi; Zoungrana Martial; Zerbo Issa (International Journal of Photoenergy)
The aim of this work is to study the behaviour of a silicon solar cell under the irradiation of different fluences of high-energy proton radiation (10 MeV) and under constant multispectral illumination. Many theoretical et experimental studies of the effect of irradiation (proton, gamma, electron, etc.) on solar cells have been carried out. These studies point out the effect of irradiation on the behaviour of the solar cell electrical parameters but do not explain the causes of these effects. In our study, we explain fundamentally the causes of the effects of the irradiation on the solar cells. Taking into account the empirical formula of diffusion length under the effect of high-energy particle irradiation, we established new expressions of continuity equation, photocurrent density, photovoltage, and dynamic junction velocity. Based on these equations, we studied the behaviour of some electronic and electrical parameters under proton radiation. Theoretical results showed that the defects created by the irradiation change the carrier distribution and the carrier dynamic in the bulk of the base and then influence the solar cell electrical parameters (short-circuit current, open-circuit voltage, conversion efficiency). It appears also in this study that, at low fluence, junction dynamic velocity decreases due to the presence of tunnel defects. Obtained results could lead to improve the quality of the junction of a silicon solar cell.